Preliminary Cytotoxicity Screening of Some Medicinal Plants of Bangladesh (Dhaka University Journal of Pharmaceutical Sciences, 2008)
The cytotoxic activity of the methanolic extracts of 35 plant species, including 28 traditionally used plants of Bangladesh was evaluated by the brine shrimp lethality bioassay technique. Among these, 19 plant extracts exhibited significant toxicity to brine shrimps with LC50 less than 10 Î¼g/ml.Key words: Cytotoxic activity, Brine shrimp lethality bioassay.DOI = 10.3329/dujps.v7i1.1217Dhaka Univ. J. Pharm. Sci. 7(1): 47-52, 2008 (June)